Rif1 promotes a repressive chromatin state to safeguard against endogenous retrovirus activation. Issue 22 (11th October 2017) - Li, Pishun; Wang, Li; Bennett, Brian D.; Wang, Jiajia; Li, Jialun; Qin, Yufeng; Takaku, Motoki; Wade, Paul A.; Wong, Jiemin; Hu, Guang
Abstract: Transposable elements, including endogenous retroviruses (ERVs), constitute a large fraction of the mammalian genome. They are transcriptionally silenced during early development to protect genome integrity and aberrant transcription. However, the mechanisms that control their repression are not fully understood. To systematically study ERV repression, we carried out an RNAi screen in mouse embryonic stem cells (ESCs) and identified a list of novel regulators. Among them, Rif1 displays the strongest effect. Rif1 depletion by RNAi or gene deletion led to increased transcription and increased chromatin accessibility at ERV regions and their neighboring genes. This transcriptional de-repression becomes more severe when DNA methylation is lost. On the mechanistic level, Rif1 directly occupies ERVs and is required for repressive histone mark H3K9me3 and H3K27me3 assembly and DNA methylation. It interacts with histone methyltransferases and facilitates their recruitment to ERV regions. Importantly, Rif1 represses ERVs in human ESCs as well, and the evolutionally-conserved HEAT-like domain is essential for its function. Finally, Rif1 acts as a barrier during somatic cell reprogramming, and its depletion significantly enhances reprogramming efficiency. Together, our study uncovered many previously uncharacterized repressors of ERVs, and defined an essential role of Rif1 in the epigenetic defense against ERV activation.